Pemberdayaan Siswa Madrasah Aliyah melalui Pelatihan Chemoentrepreneurship Lilin Hias Aromaterapi - Mohammad Agus Prayitno; Husna Amalana (LP2M of Institute for Research and Community Services - UIN Walisongo, 2019)
Islamic Senior High School of Mu'allimin Mu'allimat Rembang (MA M3R) is one of the oldest school in Rembang Regency. Most of the students who attend the school are students from various Islamic boarding schools in the city of Rembang. Most of the graduates from MA M3R did not continue to Higher Education. There are those who work, get married, and those who continue chanting. For this reason, counseling activities are needed which are to provide training to MA M3R students who aim to equip entrepreneurial skills after graduation. One of the entrepreneurial skills that can be delivered is the making of aromatherapy decorative candles. The stages in the extension activities include 3 stages, namely preparation, implementation and evaluation. This service activity is able to increase student entrepreneurial motivation, train students' tenacity and responsibility, and train good ways of communicating when marketing product results. Madrasah Aliyah Mu’allimin Mu’allimat Rembang (MA M3R) merupakan salah satu madrasah tertua di Kabupaten Rembang. Sebagian besar siswa yang bersekolah di madarah tersebut adalah santri dari berbagai pondok pesantren yang ada di kota Rembang. Sebagian besar lulusan dari MA M3R tidak melanjutkan ke Perguruan Tinggi. Ada yang bekerja, menikah, dan adapula yang melanjutkan mengaji. Untuk itu diperlukan kegiatan penyuluhan yang sifatnya memberikan pelatihan terhadap siswa-siswi MA M3R yang bertujuan untuk membekali keterampilan wirausaha setelah lulus. Salah satu keterampilan wirausaha yang dapat disampaikan adalah pembuatan lilin hias beraromaterapi. Tahapan dalam kegiatan penyuluhan ini meliputi 3 tahap, yaitu persiapan, pelaksanaan, dan evaluasi. Kegiatan pengabdian ini mampu meningkatkan motivasi wirausaha siswa, melatih keuletan dan tanggung jawab siswa, serta melatih cara berkomunikasi yang baik pada saat memasarkan hasil produk.